The Legalities of Revoking University Degrees for Misconduct: Recommendations for Australian Universities - Levine, Pnina; Evans, M. (University of New South Wales Law, Faculty of Law, 2018)
The revocation of university degrees, whilst once unheard of, has been increasingly employed by Australian universities in the wake of high-profile cheating scandals. Yet, to date, there is only one reported Australian case, Re La Trobe University; Ex Parte Hazan in which a student has challenged a university’s decision to revoke a degree. However, this case does not comprehensively address the legal issues surrounding decisions to revoke degrees. This paper therefore seeks to provide Australian universities with some clarity with respect to these issues, elucidating the source of the power of universities to revoke degrees, and the circumstances in which this power can be exercised. It does so through a review of English and United States case law, an analysis of accepted Australian administrative law principles, and an examination of university legislation in Australia.